Strategi SWOT Untuk Mengembangkan Potensi Destinasi Wisata Pantai Melayu di Kota Batam - Sarah Octavianna Simbolon; Arina Luthfini Lubis; Andri Wibowo (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2023)
The largest city in the Riau Islands is Batam. Melayu Beach, which is located on Bridge 4 Barelang, is one of the interesting places in Batam City, about a 15 minute drive from Bridge 1 or around 45 minutes drive from Batu Aji. Melayu Beach can be said to be a beach that has been operating for a long time, therefore Melayu Beach has become quiet and visitors are starting to become less interested in Melayu Beach. This causes the need for a comprehensively planned tourist destination development strategy. The qualitative descriptive research methodology was chosen for this research. Data collection techniques are as follows: questionnaires, interviews, observation, literature review, and documentation. SWOT analysis is used in research to determine how well tourist attraction development methods have succeeded in increasing the number of visitors by evaluating the advantages, disadvantages, possibilities and dangers of each strategy. Based on the results of research using the SWOT matrix with four quadrants, the IFAS and EFAS matrices, it is clear that a business diversification plan is needed to maximize the attractiveness of the Malay coast tourist attraction as well as optimize its strengths and weaknesses. The development process is as follows: (1) Expanding social media with strong branding to develop Malay beaches and distributing brochures about Barelang Malay beaches in Batam, (2) Employing local people there to manage Malay beaches so that reduce the unemployment rate and increase the economic wealth of the area surrounding the Malay coast, (3) Improve the facilities and rides on the Malay coast, and (4) Protect and maintain the ecosystem on the Malay coast.